2022
DOI: 10.1186/s13054-021-03872-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C for ≥ 5 days is associated with decreased hospital mortality in sepsis subgroups: a nationwide cohort study

Abstract: Background Previous randomized trials of vitamin C, hydrocortisone, and thiamine on sepsis were limited by short-term vitamin C administration, heterogeneous populations, and the failure to evaluate each component’s effect. The purpose of this study was to determine whether vitamin C alone for ≥ 5 days or in combination with corticosteroids and/or thiamine was associated with decreased mortality across the sepsis population and subpopulation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
3
24
0
1
Order By: Relevance
“…1 d). These findings are consistent with those in our previous nationwide cohort study that found significantly lower in-hospital mortality in sepsis patients treated with IV vitamin C for ≥ 5 days [ 4 ]. In this study, the survival curves of patients who received vitamin C for 1–2 or 3–4 days tended to diverge earlier during the course of sepsis than did those of patients treated for ≥ 5 days.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…1 d). These findings are consistent with those in our previous nationwide cohort study that found significantly lower in-hospital mortality in sepsis patients treated with IV vitamin C for ≥ 5 days [ 4 ]. In this study, the survival curves of patients who received vitamin C for 1–2 or 3–4 days tended to diverge earlier during the course of sepsis than did those of patients treated for ≥ 5 days.…”
supporting
confidence: 93%
“…In Rosengrave’s study [ 1 ], the median age of the participants was 69 years, and only 15% had comorbidities. However, our data demonstrated that these patients had lower mortality rates when vitamin C was administered [ 4 ]. Interestingly, there was no survival benefit in younger patients (< 70 years) and those with fewer comorbidities.…”
mentioning
confidence: 99%
“…A retrospective study of time sensitive mortality difference with vitamin C combination therapy indicated a significant decrease in mortality in participants who received the intervention within six hours of sepsis presentation relative to those who received it after more than six hours [ 47 ]. Furthermore, the duration of vitamin C administration is an important consideration for long-term clinical outcomes [ 48 ], with intervention for five or more days showing greater benefit [ 49 ]. Half of the intervention group in our trial did not receive the entire four days of intravenous vitamin C. Previous research has indicated that cessation of vitamin C infusions after 2–4 days can result in some patients reverting to hypovitaminosis C concentrations [ 11 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prespecified subgroup analysis stratified by the types of disease (sepsis vs. septic shock), dose [high dose was set to a daily dose of ≥100 mg/kg or 10000 mg/day, according to the review of Patel et al ( 25 )], and duration [<5 days vs. ≥5 days, according to the study by Jung et al ( 26 )] of IV vitamin C treatment. Finally, a sensitivity analysis was conducted to explore the effect of individual study by consecutive exclusion of each study at one time.…”
Section: Methodsmentioning
confidence: 99%
“…≥5 days, according to the study by Jung et al (26)] of IV vitamin C treatment. Finally, a sensitivity analysis was conducted to explore the effect of individual study by consecutive exclusion of each study at one time.…”
Section: Statistical Synthesis and Analysismentioning
confidence: 99%